Laparoscopic Cholecystectomy under Segmental Thoracic Spinal Anesthesia - Aidyl Fitrisyah; Rizal Zainal; Edi Darwis (Archives of The Medicine and Case Reports, 2021)
Introduction: Cholelithiasis or gallstones are hardened deposits of digestive fluid that can form in gallbladder. The treatment of gallstones depends upon the stage of disease. Once gallstones become symptomatic, definitive surgical intervention with cholecystectomy is usually indicated (typically, laparoscopic cholecystectomy is the first-line therapy). Laparoscopic cholecystectomy removes the gallbladder and gallstones through several small incisions in the abdomen. This case report aims to discuss the managent of segmental thoracic spinal anesthesia in laparoscopic cholecystectomy. Case: We report on the cases of 2 patients who undego elective laparoscopic cholecystectomy. Female, 53 years old, will undergo laparoscopic cholecystectomy, performed anesthesia with segmental thoracic spinal anesthesiatechnique using the anesthetic agent 3 ml of Levobupivacaine 0,5% + 25 mcg of Fentanyl, requiring a sensory block to at least T10-T11 dermatom. Patients received a 1,2 mcg target control infusion (TCI) propofol intravenous is administered as intermittent boluses to achieve deep sedation. The operation lasts 1 hour, with a bleeding 15 cc and urine output 100 cc, hemodynamically stable. Female, 42 years old, will undergo laparoscopic cholecystectomy, performed anesthesia with segmental thoracic spinal anesthesia technique using the anesthetic agent 3 ml of Levobupivacaine 0,5% + 25 mcg of Fentanyl, requiring a sensory block to at least T10-T11 dermatom. Patients received a 3 mg of midazolam intravenous is administered as intermittent boluses to achieve deep sedation. The operation lasts 1 hour, with a bleeding 15 cc and urine output 150 cc, hemodynamically stable. The level and duration of sensory block, intensity and duration of motor block were recorded. A 20 % or more decrease in MAP compared to baseline was considered as hypotension, iv ephedrine 5 mgr bolus administreted. Conclusion: Laparoscopy is a surgical procedure that uses minimally invasive surgical techniques (minimally invasive surgery) where the doctor uses a small telescope / camera that is inserted into the stomach and surgical instruments in mini form. This procedure has many advantages because it is not invasive, the amount of bleeding can be reduced, postoperative pain can be minimized. Regional anesthesia procedure in laparoscopic cholecystectomy based on several studies and case reports can be performed and is a safe procedure.